EU requirements for aquaculture planning in the member states - Bates R. (Aquaculture planning in Mediterranean countries, 1999)
No single master plan for aquaculture exists at EU level, rather the sector is supported in the context of the Common Fisheries Policy because of the positive contributions it makes in terms of stimulating economic development in coastal and rural areas where other opportunities are often limited and supplying fish and shellfish to a market which is increasingly dependent on imports. The Community has been financially committed to aquacutlure since 1971, but this was limited to freshwater until 1977. Marine and brackish water has been eligible for financial assistance since 1978. The Community structural action in favour of the development of aquaculture has been very successful to the extent that production of farmed fish and shellfish was 1,088,209 tonnes in 1997, worth 1902 million Ecu. Apart from financial and strategic planning for aquaculture the physical planning and environmental aspects are very important.
Workshop of the CIHEAM Network on Socio-economic and Legal Aspects of Aquaculture in the Mediterranean (SELAM), 1998/03/12-14, Tangiers (Morocco)